Revista Veja: uma memória LGBT e suas representações no discurso em revista - Silva, Lawerton Braga da (2022)
This thesis aimed to analyze the social representations of Lesbians, Gays, Bisexuals, Transvestites, Transsexuals and Transgenders in two different contexts. The first related to the academic environment and the scientific productions produced by Brazilian social and human sciences researchers; the second, the speeches produced by a national magazine. The first article, a systematic review of the literature, showed six classes that the articles were distributed: debate in the public scene; the role of psychoanalysis; science, justice and religion, family and possible developments; LGBT experiences and methodological issues. The review showed that groups such as Transvestites need greater attention from the academic environment. The second article analyzed during 1968 and 2018, a period of 50 years, the discourses published by the magazine Veja about the LGBT population in order to understand which social representations were being built and, also changing, throughout this period. In this sense, 5 classes were highlighted, namely: art and LGBT; diversity of sexual experiences; beyond the carnival; fight for civil rights and science, prejudice and religion. In them, it is possible to perceive the presence of scientific and religious discourse; the diversity of sexual experiences, mainly among lesbians and bisexuals; talks about representations of LGBT on television; the theme of civil rights also appears, mainly about equal marriage; finally, the evidence of a not so easy reality that transvestites live, almost always vulnerable to criminality and marginality. The thesis shows that the knowledge disseminated in these two different contexts serves to maintain consensual and reified universes that occur in social interactions, in which they do not overlap, being understood as social representations and also as science.